Meningkatkan Penguasaan Konsep Melalui Model Pembelajaran Project Base Learning Pada Materi Siklus Air - Winda Pujiyanti Sumardi; Tafhim Nur Falah; Tiara Dwi Damayanti (Indonesian Publication Center, 2024)
Natural Science (IPA) not only studies scientific concepts but also processes and the development of scientific attitudes. However, in reality, science learning is often teacher-centered, which hinders students' development of knowledge and thinking skills. This study aims to examine the effect of the Project Based Learning (PjBL) model on concept mastery and creative thinking skills of students in the topic of the water cycle in 5th-grade students at SD Negeri Cangkreplor 1. The research uses a descriptive approach with both quantitative and qualitative design. The research population consists of 32 students in 8 groups. Data were collected through observations, analysis of students’ worksheets, and documentation of group projects. The data were analyzed inferentially to assess the difference in concept mastery and creative thinking skills between the experimental group using PjBL and the control group. The main findings show that the application of PjBL improved students’ concept mastery and creativity, as evidenced by their ability to accurately depict the water cycle and creatively solve problems. Overall, the results indicate that the PjBL approach is effective in enhancing concept mastery and creative thinking skills, as well as fostering collaboration and initiative among students in learning.